RANCANG BANGUN SISTEM INFORMASI AKADEMIK BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL 10 STUDI KASUS SEKOLAH TINGGI ILMU KOMPUTER EL RAHMA: Rancang Bangun Sistem Informasi Akademik Berbasis Website Menggunakan Framework Laravel 10 Studi Kas22us Sekolah Tinggi Ilmu Komputer El Rahma - Muhammad Sandy Putra Riyadi,Suhendra Anjar Dinata, Samsuri Yahya; Suhendra Anjar Dinata (Sekolah Tinggi Ilmu Komputer El Rahma, 2025)
In today's era of digital transformation, the need for an efficient and integrated academic information system is very important for higher education institutions. El Rahma College of Computer Science faces challenges in managing complex and diverse academic data, such as student data, class schedules, attendance, and assessments. Therefore, this study aims to design and build a website-based Academic Information System using the Laravel 10 framework. This research method uses the Research and Development method. Data collection methods used in this study include observation, interviews and literature studies. The system development methods used in this study include the system approach method, system documentation model. The system approach method used is Object-Oriented Programming (OOP), while the system documentation model uses the Unified Modeling Language (UML) method which consists of various models such as use case diagrams, class diagrams, and activity diagrams. The results of the study show that the developed system has succeeded in increasing the efficiency of academic data management, facilitating access to information for students and lecturers, and providing the features needed by admins for effective data management. This system is expected to be a reliable and sustainable solution to support the academic process at El Rahma College of Computer Science.